Kebebasan Beragama di Indonesia (Studi Jemaat Ahmadiyah dalam Perspektif Majelis Ulama Indonesia dan Komisi Nasional Hak Asasi Manusia) - Muhammad Anwar Nawawi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This paper examines the meaning of religious freedom in Indonesia, the perspective of the Indonesian Ulema Council and the Indonesian National Commission especially in the context of Ahmadiyah. The essence of religion is freedom of religion. Therefore the state should protect the public interest, by guaranteeing the freedom of religion. But what happens in Indonesia as a nation state nempaknya will have difficulty to really fair to the minority. And in Indonesia Islam that becomes the majority often apply this way. This is as it is done with the flow of beliefs, or even against the Islamic groups themselves who call the Ahmadiyya school. Here there is a debate about the meaning of religious freedom between MUI and Komnas HAM. The focus of this paper is how is religious freedom in Indonesia in the perspective of MUI and Komnas HAM in the context of Ahmadiyya Jamaat?